ARTIFICIAL INTELLIGENCE IN LANGUAGE LEARNING: OPPORTUNITIES AND CHALLENGES - Ahrorova Laziza,; Khakimbayeva O.K., (TILSHUNOSLIKDA ANTROPOSENTRIZM: YANGI YONDASHUVLAR VA TADQIQOTLAR MAVZUSIDAGI RESPUBLIKA ILMIY-AMALIY ANJUMAN, 2026)
This article explores the growing influence of artificial intelligence (AI) in language education, focusing on its key benefits and limitations. In recent years, the use of AI in education has expanded significantly, with more institutions adopting intelligent technologies to improve teaching and learning processes. These innovations have significantly transformed the process of language acquisition by making it more adaptive, efficient, and learner-centered. However, despite these advantages, the use of AI also raises several concerns, including overdependence on technology, potential loss of communicative competence, and issues related to data privacy and cybersecurity. The article further emphasizes the importance of maintaining a balanced approach by combining AI tools with traditional teaching methods, promoting digital literacy, and fostering critical thinking skills among learners. Overall, while AI has the potential to greatly enhance language education, its effective integration requires careful consideration of both pedagogical and ethical factors.